2017
DOI: 10.1002/lno.10570
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling the geographical distribution of fluorescent dissolved organic matter in the surface waters of the Pacific Ocean

Abstract: Dissolved organic matter (DOM) in the epipelagic ocean is produced by marine organisms and consumed by microbes. Thus, the distributional patterns of DOM quantity and quality in surface waters are possibly related to marine ecological provinces. In this study, surface waters collected throughout the Pacific Ocean were used to investigate the geographical distributions of fluorescent DOM (FDOM) quantity and quality. An excitation‐emission matrix and parallel factor analysis revealed two humic‐like and two prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 63 publications
(129 reference statements)
2
37
1
Order By: Relevance
“…However, no significant correlation was found between protein-like C3 and Chl a (p > 0.01), suggesting that the protein-like signal was not primarily due to primary production. This contrasts with Yamashita et al (2017) and Makarewicz et al (2018), who found a positive correlation between tryptophan-like and the extracted Chl a concentration. Although protein-like FDOM is mainly derived from aromatic amino acids, such as tryptophan and tyrosine molecules in marine environments (Yamashita et al, 2015(Yamashita et al, , 2017Yamashita & Tanoue, 2003), it may also contain low molecular weight aromatics (Timko et al, 2015) such as tannins and lignins (Hernes et al, 2009;Maie et al, 2007;Yamashita et al, 2017).…”
Section: 1029/2018jc014896contrasting
confidence: 95%
“…However, no significant correlation was found between protein-like C3 and Chl a (p > 0.01), suggesting that the protein-like signal was not primarily due to primary production. This contrasts with Yamashita et al (2017) and Makarewicz et al (2018), who found a positive correlation between tryptophan-like and the extracted Chl a concentration. Although protein-like FDOM is mainly derived from aromatic amino acids, such as tryptophan and tyrosine molecules in marine environments (Yamashita et al, 2015(Yamashita et al, , 2017Yamashita & Tanoue, 2003), it may also contain low molecular weight aromatics (Timko et al, 2015) such as tannins and lignins (Hernes et al, 2009;Maie et al, 2007;Yamashita et al, 2017).…”
Section: 1029/2018jc014896contrasting
confidence: 95%
“…The lowest level of CDOM was evident in surface waters of the subtropical North Pacific (0.8-1.5 m −1 ); CDOM in surface waters of the subarctic North Pacific (1.1-1.7 m −1 ) was in the middle range. Overall, the distribution pattern of CDOM levels in surface waters was similar to that of colored dissolved and detrital material (CDM) observed by ocean color imagery (Siegel et al, 2005) and that of humic-like fluorophores determined by excitation emission matrices combined with parallel factor analysis (Yamashita et al, 2017).…”
Section: Spatial Distribution Of Dom Optical Properties In Surface Wasupporting
confidence: 56%
“…In situ quantitative correlation between chlorophyll a concentrations and fluorescence intensity of the protein-like FDOM fraction has been observed and documented recently. Yamashita et al (2017) reported significant positive correlation between the tryptophan-like component and Chla (r = 0.53, p < 0.001) in the surface waters of the Pacific Ocean. Yamashita et al (2017) also found spatial coupling between the tryptophan-like component and chlorophyll a concentration, which was strongest in the Bering Sea.…”
Section: Distribution Of Fdom Components In the Ocean And Their Depenmentioning
confidence: 93%
“…Yamashita et al (2017) reported significant positive correlation between the tryptophan-like component and Chla (r = 0.53, p < 0.001) in the surface waters of the Pacific Ocean. Yamashita et al (2017) also found spatial coupling between the tryptophan-like component and chlorophyll a concentration, which was strongest in the Bering Sea. A study by Loginova et al (2016) from a Peruvian upwelling system also reported a positively correlated chlorophyll a concentration and protein-like component (R 2 = 0.40, p < 0.001).…”
Section: Distribution Of Fdom Components In the Ocean And Their Depenmentioning
confidence: 93%
See 1 more Smart Citation